Enhancement of Androgen Action in the Kidneys of Transgenic Mice Harboring the Mutant Human UMOD Gene - Yuichi Takiue; Makoto Hosoyamada; Masaki Kimura; Hidetsugu Saito (Elsevier, 2011)
Uromodulin storage diseases are characterized by hyperuricemia of underexcretion type and renal insufficiency. Although these diseases are caused by mutations in the UMOD gene that encodes the kidney-specific glycoprotein uromodulin, the effect of uromodulin mutation on the kidney has not been clearly established. In this study, we investigated the effect by comparing transgenic mice expressing human uromodulin with and without mutation. Change in the intracellular localization of human uromodulin protein was shown in the kidney of transgenic mice expressing mutant human uromodulin by a deglycosylation experiment. Then, we determined by microarray technology and quantitative real-time PCR that the strongly induced gene in the kidney of these mice was 5-α-reductase 2, an enzyme that converts testosterone into the more potent androgen. Moreover, the expressions of androgen-induced genes β-glucuronidase, ornithine decarboxylase structural 1, and cytochrome P450 4a12a were increased. The increase in mRNA levels of urate reabsorptive transport system urate transporter 1 could be investigated, but the changes in its protein level and renal urate handling could not be demonstrated. Therefore, it is suggested that a uromodulin mutation may be responsible for the enhancement of renal androgen action.[Supplementary Table: available only at http://dx.doi.org/10.1254/jphs.10240FP] Keywords:: uromodulin, androgen, urate transport system, transgenic mice, kidney